1970
DOI: 10.1111/j.1365-2621.1970.tb00954.x
|View full text |Cite
|
Sign up to set email alerts
|

COLOR QUALITY OF FROZEN STRAWBERRIES: EFFECT OF ANTHOCYANIN, pH, TOTAL ACIDITY AND ASCORBIC ACID VARIABILITY

Abstract: SUMMARY— 40 lots of strawberries, consisting of 13 different selections and 5 varieties, were packed as frozen, sliced, sugared (4:1) fruit. Total anthocyanin content, the relative amounts of pelargonidin‐3‐glucoside and cyanidin‐3‐glucoside, ascorbic acid, pH, total acidity, soluble solids and Gardner L, a, b. determinations were made. After 9 months of storage, panel evaluation of the color quality and Gardner L, a and b determinations were taken. Results of correlation analyses indicated that pH was the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

1972
1972
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 17 publications
3
36
0
1
Order By: Relevance
“…In jams, the anthocyanins were detected only in two samples, in low amounts (0.45 and 1.07 mg/100 g FW), and as pelargonidin glycosides. The loss of anthocyanins and/or formation of brown compounds in strawberry products during processing/storage have been attributed to many factors such as pH, phenolic compounds, sugar degradation products, oxygen, ascorbic acid and also fruit maturity [20,21]. Anthocyanins are unstable, particularly once removed from the native environment which causes loss of protection afforded by the copigmentation.…”
Section: Resultsmentioning
confidence: 99%
“…In jams, the anthocyanins were detected only in two samples, in low amounts (0.45 and 1.07 mg/100 g FW), and as pelargonidin glycosides. The loss of anthocyanins and/or formation of brown compounds in strawberry products during processing/storage have been attributed to many factors such as pH, phenolic compounds, sugar degradation products, oxygen, ascorbic acid and also fruit maturity [20,21]. Anthocyanins are unstable, particularly once removed from the native environment which causes loss of protection afforded by the copigmentation.…”
Section: Resultsmentioning
confidence: 99%
“…Formation of Pg 3-gl and Cy 3-gl in the Field and in Storage In a study of 18 different strawberry genotypes, the mean total anthocyanin concentration was 573 p.M g-l and mean percentage of Pg 3-gl was 88% (Wrolstad et al 1970). …”
Section: Discussionmentioning
confidence: 99%
“…Pg 3-gl is orangered, while Cy 3-gl is magenta in color (Harborne 1984). The proportion ofPg 3-gl to Cy 3-gl can vary among genotypes of fieldripened strawberries fruit, but is generally about 88% Pg 3-gl (Wrolstad et al 1970 (Wrolstad 1976). …”
mentioning
confidence: 99%
“…The higher content of cyanidin-3-glucoside and the lower content of pelargonidin-3-glucoside in 'Oso Grande' confirm the visual observation of a more deep-red fruit at the fully red stage compared with the two other cultivars, which showed a more orange-reddish color. Wrolstad et al 49 reported previously that the different proportions of those two pigments affect the color of different strawberry varieties.…”
Section: Chemical Compositionmentioning
confidence: 99%